The sequence of the gene for cytochrome c oxidase subunit I, a frameshift containing gene for cytochrome c oxidase subunit II and seven unassigned reading frames in Trypanosoma brucei mitochrondrial maxi-circle DNA. - Hensgens, L A (1984)
A 9.2 kb segment of the maxi-circle of Trypanosoma brucei mitochondrial DNA contains the genes for cytochrome c oxidase subunits I and II (coxI and coxII) and seven Unassigned Reading Frames ("URFs"). The genes for coxI and coxII display considerable homology at the aminoacid level (38 and 25%, respectively) to the corresponding genes in fungal and mammalian mtDNA, the only striking point of divergence being an unusually high cysteine content (about 4.5%). The reading frame coding for cytochrome c oxidase subunit II is discontinuous: the C-terminal portion of about 40 aminoacids, is present in the DNA-sequence in a -1 reading frame with respect to the N-terminal moiety. URF5, 8 and 10, show a low but distinct homology (about 20%) to mammalian mitochondrial URF-1, 4 and 5, respectively. In URF5, the first AUG is found at codon 145, whereas extensive homology to mammalian URF-1 sequences occurs upstream of this position. The possibility exists that UUG can serve as an initiator codon. URF7 and URF9 have a highly unusual aminoacid composition and do not possess AUG or UUG initiator codons. These URFs probably do not have a protein-coding function. The segment does not contain conventional tRNA genes.